The fair as a space of intersection between environmental issue and health promotion (Research, Society and Development, 2022)
Fairs are rich spaces in many social aspects, including the potential to contribute to health promotion. Based on this possibility, this study aims to analyze and report an experience of health promotion action with market traders of the Green Market of Arapiraca/AL, considering the work-environment-health relationship. The first stage of the study was based on documentary research, contextualizing the social space of action. The second stage consists of an experience report, based on the research-action cycle: plan, act, describe, and evaluate. Collective planning was carried out, with the participation of sectors of the municipal government and the market vendors themselves. The action had an open nature, to be built based on the demands raised, respecting the market vendors' protagonism. The planning indicated relevance to the issue of organic waste generated by the fair, with potential to be a means of spreading diseases. Composting was elected as the strategy to be explored as an alternative to transform what, many times, is considered garbage into a beneficial product for the marketers, consumers, and society in general. The evaluation points to possibilities of continuing the action, although it requires the involvement of other academic sectors and the municipal government.